Ազգամիջյան հարաբերությունները արդի ժամանակաշրջանում (1991-2008 թթ.) - Լ. Վ. Մատինյան; Հ. Մ. Աբրահամյան (ՀՀ ԳԱԱ հրատ.)
На сегодняшний день наиважнейшим вопросом является разрешение межнациональных проблем, нередко чреватых межэтническими убийствами и кровопролитиями. При этом урегулирование подобных конфликтов должно осуществляться на государственном уровне, совместными усилиями стран, в атмосфере межнационального согласия и готовности уступить друг другу. The greatest issue of our days is, probably, the settlement of national relations and national problems, and all the possible must be implemented to stop ethnic killings, as well as bloodshed. And all mentioned must be done due to force of law, state levels, joint work, in the atmosphere of interethnic consent, tolerance towards each other and willingness to compromise.
Keywords: J Political Science; JZ International relations